The Bitch that Launched a Thousand Ships: A feminist analysis of Helen of Troy and the women of antiquity - Childs, Cierra (URJ-UCCS: Undergraduate Research Journal at UCCS, 2018)
Recent work in classics has revitalized research on the women of antiquity, both in learning more about their ideas and philosophies which may have been overlooked until now, and in reconsidering the roles that we have traditionally assumed of women in classical literature. Helen stands as the figurehead of women in antiquity, being described in homer`s Iliad and traditionally considered the cause of the Trojan War. Helens`s fame makes her an obvious candidate for feminist consideration.